A critical prospective analysis of the potential toxicity of trace element regulation limits in soils worldwide: Are they protective concerning health risk assessment? - A review. (June 2019) - Antoniadis, Vasileios; Shaheen, Sabry M.; Levizou, Efi; Shahid, Muhammad; Niazi, Nabeel Khan; Vithanage, Meththika; Ok, Yong Sik; Bolan, Nanthi; Rinklebe, Jörg
Abstract: Trace elements (TEs) may have toxic effects to plants and humans; thus, countries and organizations impose maximum allowable regulation limits of their concentrations in soils. Usually such limits are placed in different categories according to soil use, soil properties or based on both attributes. However, some countries have regulation limits irrespective of differentiation in soil properties. In this review, we aimed at collecting TE regulation limits in soils from major countries and organizations around the globe, and critiquing them by assessing potential human health risks in the case of soils attaining the maximum allowable values. We explored the soil-to-human pathway and differentiated among three major exposures from TEs, i.e., residential, industrial and agricultural. We observed the existence of problems concerning TE regulation limits, among which the fact that limits across countries do not regulate the same TEs, not even a minimum number of TEs. This indicates that countries do not seem to agree on which regulation limits of TEs pose a high risk. Also, these regulation limits do not take into account TE mobility to neighbouring environment interphases such as plant, especially edible, and water matrices. Moreover, limits for same TEs are vastly diverse across countries; this indicates that those countries have conflicting information concerning TE-related health risks. Subsequently, we addressed this problem of diversity by quantifying resultant risks; we did that by calculating human health risk indices, taking into consideration the cases in which the highest allowable TE limits are attained in soil. Arsenic limits were found to generate a relatively high hazard quotient (HQi, accounting for human intake over the maximum allowable oral reference dose for that same TE), indicating that its risk tends to be underestimated. Other TE limits, such as those of Cd, Cu, Ni, Pb, and Zn typically result in low HQi, meaning that limits in their cases are rather overprotective. Our approach reveals the need of reducing diversity in regulation limits by drafting soil legislations of worldwide validity, since risks are common across countries. We suggest that new directions should strategically tend to (a) reduce limits of TEs with underestimated contribution to health risk (such as As), (b) cautiously increase limits of TEs that currently cause minor health risks, (c) quantify TE risks associated with uptake to edible plants and potable water, and (d) consider multi-element contamination cases, where risks are cumulatively enhanced due to TE synergism. Graphical abstract: Unlabelled Image Highlights: Trace element (TE) regulation limits around the globe are highly diverse. Regulation limits across countries regulate different trace elements. Arsenic limits generate high hazard quotients (HQ), thus they must be reconsidered. Cadmium, Cu, Ni, Pb and Zn limits result in low HQ—thus they are overprotective. Risks associated with uptake to edible plants and potable water must be implemented.